Relevant Ongoing Clinical Trials to Investigate Local‐Regional Treatment Strategies for Peritoneal Surface Malignancies - Blaj, S.; Häusler, S.; Piso, P. (Journal of surgical oncology, 2024)
ABSTRACT Background and Objectives The multimodal therapy of peritoneal metastases of common cancers (i.e. colorectal, gastric, and ovarian), including CRS plus HIPEC, is still subject to several clinical studies. Methods This paper presents the ongoing studies regarding HIPEC, as found on clinicaltrials.gov. The emphasis was set on Phase III recruiting trials, including the newest information from principal investigators who answered the call of the authors. Results Ninety trials have been identified, and the protocols of 15 studies have been presented in detail. Conclusions There are interesting ongoing trials investigating the role of CRS plus HIPEC.